On the use of global–local kinematic coupling approaches for delamination growth simulation in stiffened composite panels. (12th August 2015) - Borrelli, R.; Riccio, A.; Sellitto, A.; Caputo, F.; Ludwig, T.
Abstract: This paper investigates kinematic coupling approaches for FE simulation of the mechanical behavior of complex composite structures. Two coupling methods belonging to the family of kinematic coupling approaches, namely the point-wise kinematic coupling and the weighted residual kinematic coupling are analyzed and assessed with respect to their application to non-linear structural FE analyses. The investigated kinematical coupling approaches have been implemented in the in B2000++ FEM code developed by SMR® and used to couple global–local domains characterized by different mesh refinements. A stiffened composite panel with an artificial bay delamination under compressive load has been adopted as numerical benchmark. Results in terms of stress distributions at domains interfaces, obtained with several FE models characterized by different coupling approaches and different mesh refinements, have been compared with the results obtained adopting a reference test-case model with mesh continuity and merged modes. Furthermore, the influence of the coupling approach on the delamination growth simulation has been assessed. Finally considerations about the computational effectiveness of the coupling approaches with respect to the reference test-case are introduced.